IDENTIFICATION OF PROSPECTIVE TEACHER'S SCIENTIFIC REASONING ABILITY USING THE LAWSON CLASSROOM TEST OF SCIENTIFIC REASONING (CTSR) - Hidayah, Nurul; Arafah, Rezqy Ayu Devi (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
The aim of study was conducted to determine the scientific reasoning ability of prospective elementary school teacher students. The type of research conducted was non-experimental quantitative research. The instrument used to identify students' scientific reasoning ability was the Lawson's Classroom Test of Scientific Reasoning (CTSR). The test sample was 28 fifth-semester PGSD students. These prospective elementary school teacher students were given scientific reasoning questions in the form of multiple-choice questions containing mass and volume conservation, proportional reasoning, controlling variables, probabilistic reasoning, correlation reasoning, and hypothesis-deductive reasoning. Furthermore, the students' answers will be categorized according to Piagetian which includes concrete reasoning, early transition reasoning, late transition, and formal reasoning. The results showed that the level of concrete reasoning was 18%, early transition was 68%, while the late transition was 14%, and formal reasoning was 0%. These results indicate that the reasoning ability for prospective elementary school teacher students is still relatively low, there needs to be an improvement in learning methods that pay more attention to scientific reasoning abilities so that they can improve their scientific reasoning abilities.. ABSTRAKPenelitian dilakukan untuk mengetahui kemampuan penalaran ilmiah mahasiswa calon guru SD. Jenis penelitian yang dilakukan adalah penelitian kuantitatif non eksperimen. Instrumen yang digunakan untuk mengidentifikasi kemampuan penalaran ilmiah mahasiswa adalah Lawson’s Classroom Test of Scientific Reasoning (CTSR). Sampel uji sebanyak 28 mahasiswa PGSD semester lima. Para mahasiswa calon guru SD ini diberikan soal penalaran ilmiah berupa butir soal pilihan ganda beralasan yang memuat konservasi massa dan volume, penalaran proporsional, mengontrol variabel, penalaran probabilistik, penalaran korelasi, dan penalaran hipotesis-deduktif . Selanjutnya jawaban mahasiwa akan di kategorikan sesuai dengan piagetian yang mencakup penalaran konkret, penalaran transisi awal, transisi akhir, dan penalaran formal. Hasil penelitian menunjukkan bahwa tingkat penalaran konkret sebesar 18%, transisi awal sebesar 68%, sedangkan transisi akhir 14%, dan penalaran formal sebesar 0%. Hasil tersebut menunjukkan bahwa kemampuan penalaran untuk mahasiswa calon guru SD masih tergolong rendah, perlu adanya perbaikan metode pembelajaran yang lebih memperhatikan pada kemampuan penalaran ilmiah sehingga dapat meningkatkan kemampuan penalaran ilmiahnya.